Perspectiva semiótica na autobiografia: o que é isso, companheiro? - Mathias, Rafaela Reino (Universidade Federal de São Carlos, 2026)
This study examines the relationship between Brazilian literature and the military regime, considering literature as a key source for understanding the censored history of the dictatorship. It analyzes O que é isso, companheiro? (1996), by Fernando Gabeira, through the lens of discursive semiotics, focusing on syntactic and semantic-discursive levels to identify meaning effects. The research also draws on tensive grammar, as proposed by Jacques Fontanille and Claude Zilberberg (2001), to explore the notions of field of presence and event in autobiographical discourse.Based on Mariana Luz Pessoa de Barros (2016), particularly the concepts of the memory of the past event and the event memory, the study finds that Gabeira’s narrative primarily reconstructs lived experiences from a distanced perspective, characteristic of the memory of the past event. However, it also incorporates elements of the event memory, creating a degree of sensorial engagement that brings the reader closer to the narrated experience. The results indicate that the work articulates both documentary and experiential dimensions, functioning not only as a historical record but also as a narrative that produces effects of presence and meaning in the social sphere.
Semiotic perspective on the autobiography: o que é isso, companheiro?
Keywords: Ditadura miltiar brasileira; Semiótica; Literatura; Discurso autobiográfico; Documento; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; 4. Educação de Qualidade